Combining the unequal variance signal detection model with the health belief model to optimize shared decision making in tinnitus patients: part 2—patient profiling - Zsófia Zs Lehóczky; Zsófia Zs Lehóczky; Adriana L. Smit; Adriana L. Smit; Sarah Kaldenbach; Arnold Lieftink; Arnold Lieftink; Huib Versnel; Huib Versnel; Robert J. Stokroos; Robert J. Stokroos; Alexander E. Hoetink; et al. (Frontiers in Neuroscience)
IntroductionTinnitus affects approximately 14% of the population. Its symptomatology is versatile, ranging from mild annoyance to anxiety and depression. Current multidisciplinary treatments (psychological, audiological, and combinations) focus on impact reduction and acceptance. Shared decision making (SDM) promotes patients and health care professionals making treatment choices together based on the best available evidence. In the case of professional equipoise (no clear clinical evidence for superiority of a treatment), knowledge about individual factors influencing the outcome of patient decisions can be of utmost importance in informing the SDM process.MethodsA statistical model that was developed in previous work to analyze tinnitus patient decisions, was extended to analyze how patient characteristics on sex, age, and laterality of tinnitus affect the accuracy and utility of decisions concerning audiological care and cognitive behavioral therapy (CBT) based psychosocial counseling. For each group, we calculated Receiver-Operator-Characteristic curves and likelihood ratio curves as function of hearing loss and pre-treatment tinnitus impact to assess accuracy and utility of decisions for audiological care and CBT-based counseling, respectively.ResultsThe largest effect was found for sex differences. The results indicated that males used a strict decision criterion when deciding about psychosocial counseling, while females used a strict decision criterion for decisions about audiological care. The likelihood ratios of a successful treatment versus unsuccessful treatment are smaller than 1 for psychosocial counseling for females and for audiological care for males. The likelihood ratios of success are approximately 2 and almost 7 for audiological care for females and psychosocial counseling for males, respectively. For age differences, older participants adopted a more lenient decision criterion for audiological care across most of the hearing loss range, while younger participants adopt a stricter decision criterion up to hearing losses of approximately 75 dB(HL). For psychosocial counseling, older participants adopted an unbiased criterion and younger participants a strict decision criterion. For the younger group, psychological counseling seems more likely to be successful compared to the older group. When considering laterality, for audiological care the group with unilateral tinnitus adopted a strict decision criterion for the whole range of hearing loss, while the group with bilateral tinnitus adopted a strict decision criterion for hearing losses above approximately 70 dB(HL). For decisions about psychosocial counseling, the unilateral tinnitus group adopt a strict decision criterion for baseline THI-scores between approximately 25 and 90 points. The bilateral tinnitus group adopted an unbiased to strict decision criterion for psychosocial counseling for the entire baseline THI-score range.DiscussionThese findings underscore the importance of personalized treatment approaches based on specific patient characteristics and the need for further research to test and improve these findings. Especially males may be more strongly advised to take up psychosocial counseling and females may be more strongly advised to take up audiological care. For age and laterality, the results are more diffuse.